Analysis of axial windage loss in air gap of high-speed motors under high Taylor number. Issue 1 (1st February 2023) - Song, Yuchen; Cao, Jiwei; Zhong, Chengbao; Chen, Jialiang; Li, Liyi
Abstract: In the field of ultra-high-speed motors, windage loss rises rapidly with the increase of rotational speed, and even becomes the main part of motor loss. However, most researches of windage loss are based on empirical formulas, which has a narrow scope of application. These formulas could not guarantee the accuracy when calculating large Taylor number flow in high-speed motor air gap, especially under axial ventilation condition. This paper focuses on the interaction between Taylor vortices and axial flow, analyses the influence of Taylor number on the behaviour of Taylor vortices and windage loss under non-axial and axial ventilation. First, another form of friction coefficient related to rotation speed is proposed using dimension analysis. Second, the scale of Taylor vortices is estimated and how it affects windage loss is discussed. Finally, a deceleration experiment taking a 250krpm induction motor is used to verify the accuracy of the proposed windage loss model.